Inverse poroelasticity as a fundamental mechanism in biomechanics and mechanobiology - Alexander E. Ehret (Nature Portfolio, 2017)
How soft tissues respond to mechanical load is essential to their biological function. Here, the authors discover that – contrary to predictions of poroelasticity – fluid mobility in collagenous tissues induces drastic volume decrease with tensile loading and pronounced chemo-mechanical coupling.